Scuba diving with the grey nurse shark (Carcharias taurus): an application of the theory of planned behaviour to identify divers beliefs. Issue 2 (8th January 2014) - Apps, Kirin; Lloyd, David; Dimmock, Kay
Abstract Scuba diving with the critically endangered grey nurse shark (Carcharias taurus) is a popular attraction for divers on the east coast of Australia. As the popularity of shark diving develops globally, research is required to evaluate how diving with sharks affects the behaviour and ecology of the species. Understanding participant's behaviour when diving with C. taurus can provide valuable information for researchers and policy makers trying to conserve this species. An elicitation procedure based on the theory of planned behaviour was applied to determine divers' beliefs pertinent to approaching C. taurus when scuba diving at two sites on Australia's east coast. A content analysis of responses revealed preliminary insights into the salient beliefs of divers. This initial step is an essential foundation for subsequent phases of research and communication aimed at improving shark and diver interactions and experiences. Copyright © 2014 John Wiley & Sons, Ltd.